Inovasi Pendidikan Islam Pada Perkembangan Madrasah Menghadapi Tantangan Perubahan - Simatupang, Wandana; Wasiyem, Wasiyem; Syukri, Makmur (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The emergence of educational innovation in Indonesia is a creative and progressive response of leaders and experts and educators in implementing the national education system. The strategic role of planners, program implementers, and evaluators to respond to all internal and external changes requires a positive response to all events that shake managerial power, human resources, and organizational culture in schools, madrasas, and Islamic boarding schools to be able to carry out change or innovation. Because educational innovation necessitates a renewal in management, curriculum, learning technology with networks and modernization of educational facilities and infrastructure. This paper examines the idea of ​​the importance of Islamic education innovation in madrasas, pesantren and Islamic religious schools as a sub-system of national education.